Pemanfaatan Lindi Menjadi Kompos Melalui Budidaya Larva Black Soldier Fly (BSF) - Safitri Nurkomariyah; Rachmanto, Tuhu Agung (Yayasan Literasi Sains Indonesia, 2023)
Leachate, a byproduct of water entering landfills, contains high amounts of organics, acids, metals, and dissolved salts, posing environmental risks. Due to leachate can be hazardous and there are few remediation alternatives, researchers are exploring leachate reduction methods using decomposing organisms like Black Soldier Fly (BSF) larvae. This research investigates BSF larvae's ability to decompose leachate, determines the quality of the final residue and analyzes the growth of the larvae. BSF larvae were grown for 12 days on a mixture of substrate and leachate. The variations used are the solvent content of the leachate solution (75%, 50%, 25%, and 0% solvent) and the type of substrate (bran, tofu dregs, or a mixture of tofu bran-dregs). Using leachate in raising BSF larvae effectively degrades leachate and creates standardized organic fertilizer. The substrate type and solvent content of the leachate solution affect media reduction. As the solvent gets smaller or the leachate concentration increases, the medium shrinks more. The highest media shrinkage of 58.83% is achieved by combining bran and tofu dregs with 0% leachate solution solvent concentration.